ENTREPRENEURSHIP MINDSET AND INNOVATION AS STRATEGIES TO STRENGTHEN BUSINESS INCUBATOR ECOSYSTEMS IN PROMOTING MSME SUSTAINABILITY - Liena Prajogi1; Humiras Betty Marlina Sihombing; Vickrie Ardy (Graduate Program of Universitas Tarumanagara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a backbone of Indonesia’s economy, yet their sustainability is challenged by limited digital literacy, weak access to financing, and insufficient innovation capacity. Business incubators emerge as a strategic mechanism to strengthen MSMEs by providing mentoring, networking, and access to resources. This study aims to analyze the role of entrepreneurship mindset and innovation in enhancing business incubator ecosystems and their contribution to MSME sustainability. The research employed a qualitative approach, combining a Systematic Literature Review (SLR) with a single case study at the MNC University Business Incubator. Thematic content analysis was used to synthesize prior studies, while pattern matching was applied to validate findings within the case context. Results reveal that entrepreneurship mindset covering opportunity orientation, creativity, risk-taking, and resilience and innovation across product, process, and business model are key inputs in reinforcing incubator ecosystems. The MNC University case demonstrates that integration of mentoring, digital platforms, and multi-actor collaboration aligns with the Triple Helix and Quadruple Helix frameworks, thereby enhancing MSME competitiveness and sustainability. This study contributes theoretically by linking mindset and innovation to incubator ecosystem development, and practically by offering insights into higher-education-based incubator practices that can be replicated in similar contexts.